Pregunta
\[ \text{Find } 2011^2 - 2010^2 \text{?} \]
Ask by Savage Riley. in South Africa
Feb 16,2025
Solución de inteligencia artificial de Upstudy
Respuesta verificada por el tutor
Responder
The answer is 4021.
Solución
We can use the difference of squares formula:
a² - b² = (a + b)(a - b).
Here, a = 2011 and b = 2010, so:
2011² - 2010² = (2011 + 2010)(2011 - 2010) = (4021)(1) = 4021.
Thus, the answer is 4021.
Respondido por UpStudy AI y revisado por un tutor profesional
Como
error msg
![](/pmw/light_bulb.png?etag=525fd69ac661e11754e2fc9f1b18a4ee)
![](/pmw/spiral_notepad.png?etag=abe3906b7558c543a7b30ba53a3b5a5b)
Bonus Knowledge
To find \( 2011^2 - 2010^2 \), we can use the difference of squares formula, which states that \( a^2 - b^2 = (a-b)(a+b) \). In this case, let \( a = 2011 \) and \( b = 2010 \). Calculating the values: \[ a - b = 2011 - 2010 = 1 \] \[ a + b = 2011 + 2010 = 4021 \] Now we can apply the difference of squares formula: \[ 2011^2 - 2010^2 = (2011 - 2010)(2011 + 2010) = 1 \times 4021 = 4021 \] So, \( 2011^2 - 2010^2 = 4021 \).
![](/pmw/img-try-permium.webp)
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium